An Empirical Analysis of Financial Risk Tolerance and Demographic Factors of Business Graduates in Pakistan - Shah, Naveed Hussain; Khalid, Waqar; Khan, Saifullah; Arif, Muhammad; Khan, Muhammad Asad (International Journal of Economics and Financial Issues, 2020)
The purpose of this empirical study was to investigate whether financial risk-tolerance differs among business graduates in Pakistan based on their demographic factors (i.e., gender, age, education, experience, income, saving, location, and occupation). This study has tested the financial risk-tolerance scale developed by Grable and Lytton (1999) to empirically measure the different dimensions of financial risk. The study employed a quantitative approach to a multinomial logistic regression model and an online questionnaire tool for the primary data collection. The well-designed questionnaires were distributed among business graduates through online media. The empirical findings of the study depicted a significant positive effect from all the demographics against financial risk-tolerance. Specifically, the results showed that male business graduates having more income and savings, those with more education qualifications and also older graduates are positively related to financial risk-tolerance. However, the relationship between financial risk-tolerance and experience level of individuals was found negative and insignificant, and the same result between the two variables can be confirmed by the findings of the correlation analysis. Furthermore, the parametric study showed that geographical differences exist among business graduates in terms of financial risk-tolerance attitudes. Keywords: Risk tolerance; Demographic factors; Financial risk; Multinomial logistic regression; Cross regions. JEL Classifications: G1, G32, G41 DOI: https://doi.org/10.32479/ijefi.9365